Augmented reality for constructivist learning at work: current perspectives and future applications - Bödding, Rabea; Bentler, Dominik; Maier, Günter W. (Gruppe. Interaktion. Organisation. Zeitschrift für angewandte Organisationspsychologie, 2023)
This manuscript for the journal Gruppe. Interaktion. Organisation. (GIO) addresses the use of a new and very promising technology for work-related learning, Augmented Reality. New technological solutions have and continue to impact work in different areas, one of which is work-related learning. While Augmented Reality has been subject to numerous studies in the context of work and work training, there is a need for more detailed discussion of its relation to the theoretical foundations of learning and the therein based implications for designing and testing learning environments in Augmented Reality. For this purpose, our paper first reviews current perspectives on Augmented Reality and its value for work-related learning, before introducing and examining the concept of Instructional Design Methods. These are abstract mechanisms that can be used to support training using Augmented Reality based on expert performance. Through thorough discussion of these methods, we pose new perspectives on their application for future research and practical application.